2016
DOI: 10.1159/000444216
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index Predicts Progression of Mild Cognitive Impairment to Dementia

Abstract: Aims: To examine the relationship between body mass index (BMI) and progression to dementia and Alzheimer's disease (AD) in mild cognitive impairment (MCI). Materials and Methods: Two hundred and twenty-eight MCI subjects (mean age 74.04 ± 6.94 years; 57% female) from a memory clinic were followed for 2.40 ± 1.58 years. Baseline height and weight were used to calculate the BMI. The main outcome was progression to dementia (DSM-IV criteria) and AD (NINCDS-ADRDA criteria). Cox proportional hazard models were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
27
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 40 publications
(47 reference statements)
6
27
1
Order By: Relevance
“…There were many potential risk factors for cognitive impairment, such as sex, age, body mass index and blood pressure (Stein et al 2012;Cova et al 2016;Tully et al 2016). However, the present study did not find any differences in sex, age and body mass index between the MCI patients and the non-MCI subjects.…”
Section: Mmsecontrasting
confidence: 86%
“…There were many potential risk factors for cognitive impairment, such as sex, age, body mass index and blood pressure (Stein et al 2012;Cova et al 2016;Tully et al 2016). However, the present study did not find any differences in sex, age and body mass index between the MCI patients and the non-MCI subjects.…”
Section: Mmsecontrasting
confidence: 86%
“…First, some lifestyle information, laboratory records on inflammatory biomarkers, family history, and genetic factors are not available in the LHID2005. These factors are considered to affect cognitive function and might confound the association between prior RA and AD [3537]. Second, the LHID2005 provides no detailed records of biochemical tests, Mini-Mental State Examination (MMSE) scores, or medical imaging.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are few studies on the relationship between BMI and AD in MCI subjects. A recent study of 228 MCI subjects reported that the overweight or obese group had a reduced risk of both dementia and AD, while the underweight group had a higher risk of dementia but not AD, compared to the normal weight group [ 8 ]. Other study has investigated this relationship in MCI subjects, suggesting that, the underweight group had a higher risk while the obese group had a lower risk of AD compared to the normal weight group [ 9 ].…”
Section: Introductionmentioning
confidence: 99%